(untitled) (Journal of the Bangladesh Agricultural University, 2012)
A total of 60 day old straight run pekin ducklings were fed ad libitum on 6 diets viz, D1- 15% parboiled rice polish (PRP) based diet, D2- D1 + Mixed enzyme (Carbohydrase 120 ppm/kg + phytase 1000FYT/kg), D3- 25% parboiled rice polish (PRP) based diet, D4 - D3 + Mixed enzyme ( Carbohydrase 120 ppm/kg + phytase 1000FYT/kg), D5-35% parboiled rice polish (PRP) based diet, D6 - D5+ Mixed enzyme ( Carbohydrase 120 ppm/kg + phytase 1000FYT/kg) for 84 days. Diets were supplied two stages containing 22.5, 22.5, 22.8% CP for starter and 16.4, 16.9, 17% CP for finisher. Increasing PRP levels without enzyme decreased live weight, feed intake and feed conversion but increase profitability without affecting livability. Addition of mixed enzyme promoted growth, feed conversion significantly (P<0.01), but did not alter livability. The rate of improvement in performance for enzyme supplementation increased with increasing level of dietary PRP. Therefore, it was concluded that it is possible to reduce costly grain by using PRP in duck ration and supplementation of phytase and carbohydrase in PRP diet may be beneficial to improve performance of ducks. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12100 J. Bangladesh Agril. Univ. 10(1): 101106, 2012